YAP suppresses gluconeogenic gene expression through PGC1α. Issue 6 (30th October 2017) - Hu, Yue; Shin, Dong‐Ju; Pan, Hui; Lin, Zhiqiang; Dreyfuss, Jonathan M.; Camargo, Fernando D.; Miao, Ji; Biddinger, Sudha B.
Abstract : Cell growth and proliferation are tightly coupled to metabolism, and dissecting the signaling molecules which link these processes is an important step toward understanding development, regeneration, and cancer. The transcriptional regulator Yes‐associated protein 1 (YAP) is a key regulator of liver size, development, and function. We now show that YAP can also suppress gluconeogenic gene expression. Yap deletion in primary hepatocytes potentiates the gluconeogenic gene response to glucagon and dexamethasone, whereas constitutively active YAP suppresses it. The effects of YAP are mediated by the transcriptional coactivator peroxisome proliferator–activated receptor‐gamma coactivator 1. YAP inhibits its ability to bind to and activate transcription from the promoters of its gluconeogenic targets, and the effects of YAP are blunted upon its knockdown. In vivo, constitutively active YAP lowers plasma glucose levels and increases liver size. Conclusion : YAP appears to reprogram cellular metabolism, diverting substrates away from the energy‐consuming process of gluconeogenesis and toward the anabolic process of growth. (Hepatology 2017;66:2029–2041)